Skills Teacher Creativity in Overcoming Limited Learning Facilities at SMP Negeri 6 South Halmahera - Jumrah Jamil (Formosa Journal of Applied Sciences, 2023)
This research aims to examine and analyze Teacher Creativity Skills in Overcoming Limited Learning Facilities at SMP Negeri 6 South Halmahera. This paper was written using library research techniques. Reference materials used in this essay include published books and scientific publications. The purpose of this article is to learn how teachers at SMP Negeri 6 South Halmahera use their creativity to overcome classroom shortages. Findings According to research, 1) skills learning resources and infrastructure are inadequate; 2) the condition of the infrastructure is not good due to the age of the equipment; and 3) the teacher's creative attitude is shown by his ability to recognize problems and look for concepts in skills learning.